Из Именного указателя к «Записным книжкам» Ахматовой: Джон Китс [From an Index to Anna Akhmatova’s _Notebooks_: John Keats] - Timenchik, Roman (Slavica Revalensia, 2022)
This is a yet another installment in the series of Roman Timenchik’s annotations to Anna Akhmatova’s _Notebooks_ (see also four previous volumes of Slavica Revalensia — from 2018 to 2021). This particular installment examines Akhmatova’s appreciation of John Keats: the poet she mentioned in _Notebooks_ as the source of the epigraph to the cycle “Shipovnik tsvetet” (“The Rosehip Blossoms”), and also a poet she read extensively while learning English in Tashkent. The article proves that this learning experience left echoes in several of Akhmatova’s poems of the corresponding period, and also examines Akhmatova’s interest and appreciation of Keats vis-à-vis the background of the British poet’s reception by some of her contemporaries.